Pewarnaan Gram Buffy Coat untuk Deteksi Awal Pasien Bakteremia - leka lutpiatina (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2015)
Abstract: Bacteremia is one public health problem. Bacteremia was ranked as the tenth leading cause of death in the United States. Gram staining of buffy coat can be used for early detection of patients with bacteremia. Rapid diagnostic tests with these Gram staining can be interpreted within an hour and the research that has been conducted Richmond et al. 2002, have a sensitivity of 75% and specificity of 79%. This study aimed to study the sensitivity and specificity of Gram buffy coat with the gold standard blood culture media biphasic fever suspected patients. This study was an observational study with cross sectional study. The study population was suspected fever patients in hospitals Ratu Zalecha Martapura months from March to May 2013. The samples were suspect fever patients in hospitals Queen Zalecha Martapura March-May 2013 were taken by purposive with the inclusion criteria: Patients District General Hospital Ratu Zalecha Martapura, aged ≥10 years, had fever ≥ 5 days, had symptoms of abdominal pain, willing to follow the study. Gram staining microscopic results were analyzed by application epicalc. Microscopic results buffy coat Gram staining Gram-negative rods are found as many as seven (26%) and were not found Gram-negative rods as many as 20 (74%). Culture results of this study are Gram negative bacterial growth as much as 6 (22%) and no growth as many as 21 (78%). Conclusion The results of microscopic Gram stain buffy coat has a value of 67% sensitivity and 86% specificity.